Monomer modifications of denture base acrylic resin: A systematic review and meta-analysis - R Ajay; K Suma; Seyed Asharaf Ali (Wolters Kluwer Medknow Publications, 2019)
Background: Methyl methacrylate monomer of denture base resins was modified with several monomers to achieve better physico-mechanical properties without compromising the biocompatibility. However, there are no consensuses on the best strategy to achieve best modified monomer. Purpose: To identify and evaluate the differences in the properties between conventional and modified monomers and to verify the influence of several variables on the properties of denture base acrylic resin. Materials and Methods: This study was executed by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. In-vitro studies that investigated the properties of conventional and modified monomers were selected. Searches were carried out in the Ebscohost, PubMed, Semantic scholar and J-stage databases. The search commenced from the year 1995 and the last search was done till November 2018. A comparison was performed between modified and unmodified monomers. The analyses were carried out using fixed-effect models. Results: The meta-analysis results showed high heterogeneity in all aspects, and higher flexural strength for monomers modified with 20% methacrylic acid. Conclusion: Although the articles included in this meta-analysis showed high heterogeneity and high risk of bias, the in-vitro literature seems to suggest that use of modified monomers could improve the properties of denture base resins. Other variants of monomer modifications and their tested parameters were discussed in this systematic review as well. Dimensional accuracy is an unexplored variable to be evaluated extensively in the future researches.